PENGARUH PENGATURAN JARAK TANAM DAN PUPUK NITROGEN TERHADAP PERTUMBUHAN DAN HASIL TANAMAN SORGUM (Sorghum bicolor L. Moench) Varietas Samurai 2 - Irfan,, Achmad; Faqih, Achmad; Nur, Subandi (Prodi Agronomi Pascasarjana Universitas Swadaya Gunung Jati, 2024)
This experiment aims to determine the effect of spacing and nitrogen fertilizer on the growth and yield of sorghum (Sorghum bicolor L. Moench) Samurai 2 variety. The experiment was carried out in Mekarjaya Village, Gantar District, Indramayu Regency - West Java. The time of the research was carried out from July to November 2021. The location is located at an altitude of 493 m above sea level (asl), the soil type is the association of Latosol and Regosol, including type C rain (slightly wet). The experimental method used is the experimental method with a factorial randomized block design (RAK), the treatment consists of two factors, repeated three times. The first factor is nitrogen fertilizer which consists of three levels, namely 100 tons/ha nitrogen fertilizer, 150 tons/ha nitrogen fertilizer, and 200 tons/ha nitrogen fertilizer. While the second factor is the spacing which consists of three levels, namely the spacing of 25 cm x 40 cm, the spacing of 25 cm x 50 cm, and the spacing of 25 cm x 60 cm. The main observation data were processed using linear model statistical tests, analysis of variance, and Scott-knot cluster further test analysis. To determine the correlation between the treatment with the components of growth and yield of sorghum, the correlation used is the Product Moment correlation coefficient. 1 The experimental results showed: (1) The combination of plant spacing and nitrogen fertilizer had an effect on leaf area index at 28 HST, 35 HST and 42 HST, and panicle length, but had no significant effect on plant height, number of leaves, stem diameter, root volume, number of panicles per clump, panicle weight per clump, 1000 seed weight, seed weight per clump and dry seed weight per plot, (2) The highest seed weight per plot was produced by the combination of treatment G, namely 25cm x 60 cm spacing and 100 kg urea fertilizer with an average The average weight was 3.79 kg (equivalent to 6.314 tons/ha), but it was not significantly different from the other treatment combinations, (3) There was a significant correlation between plant height at 42 HST and seed weight per plot in the tall category. However, there was no significant correlation between plant height at 28 HST (very low category) and 35 HST (low category) and the number of leaves at 28 HST (very low category), 35 HST (very low category) and 42 HST (very low category). low category) with dry seed weight per plot